2010
DOI: 10.1194/jlr.m004978
|View full text |Cite
|
Sign up to set email alerts
|

Activation of LXR increases acyl-CoA synthetase activity through direct regulation of ACSL3 in human placental trophoblast cells

Abstract: This article is available online at http://www.jlr.org thetases (ACSL), the fatty acid transport proteins (FATP), and the acyl-CoA synthetase bubblegum (ACSBG) family ( 1-5 ). Five genes in the ACSL family have been identifi ed based on sequence homology. They are named ACSL1 and ACSL3 to ACSL6 and differ in their tissue and intracellular distribution. The distinct intracellular location of acyl-CoA synthetases has been hypothesized to channel fatty acids to different metabolic fates by activating the fatty ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 61 publications
(71 reference statements)
1
40
0
Order By: Relevance
“…Activation of LXRs by endogenous ligands of oxidized cholesterol derivatives and pharmaceutical agonists leads to induction of genes involved in reverse cholesterol transport and mobilization of cholesterol, such as the ATP binding cassette (ABC) transporter genes ABCA1, ABCG1, ABCG5, and ABCG8, and genes involved in bile acid synthesis, such as CPY7A ( 25,26 ). Interestingly, a recent report has shown that treating placental trophoblast cells with LXR synthetic ligands stimulated ACSL3 gene transcription, and this effect was mapped to a LXRE motif located 163 bp upstream of the transcription start site ( 27 ), which is downstream of PPRE sites. This study further showed that in cultured human placental BeWo cells, in addition to ACSL3, ACSL5 and ACSL6 were induced by an LXR agonist, implying that these three ACSL isozymes could all be the downstream targets of LXR signaling pathways ( 27 ).…”
Section: Animal Dietsmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of LXRs by endogenous ligands of oxidized cholesterol derivatives and pharmaceutical agonists leads to induction of genes involved in reverse cholesterol transport and mobilization of cholesterol, such as the ATP binding cassette (ABC) transporter genes ABCA1, ABCG1, ABCG5, and ABCG8, and genes involved in bile acid synthesis, such as CPY7A ( 25,26 ). Interestingly, a recent report has shown that treating placental trophoblast cells with LXR synthetic ligands stimulated ACSL3 gene transcription, and this effect was mapped to a LXRE motif located 163 bp upstream of the transcription start site ( 27 ), which is downstream of PPRE sites. This study further showed that in cultured human placental BeWo cells, in addition to ACSL3, ACSL5 and ACSL6 were induced by an LXR agonist, implying that these three ACSL isozymes could all be the downstream targets of LXR signaling pathways ( 27 ).…”
Section: Animal Dietsmentioning
confidence: 99%
“…Interestingly, a recent report has shown that treating placental trophoblast cells with LXR synthetic ligands stimulated ACSL3 gene transcription, and this effect was mapped to a LXRE motif located 163 bp upstream of the transcription start site ( 27 ), which is downstream of PPRE sites. This study further showed that in cultured human placental BeWo cells, in addition to ACSL3, ACSL5 and ACSL6 were induced by an LXR agonist, implying that these three ACSL isozymes could all be the downstream targets of LXR signaling pathways ( 27 ).…”
Section: Animal Dietsmentioning
confidence: 99%
See 1 more Smart Citation
“…Key regulators of lipid metabolism modify the expression of ACSL3: The LXR nuclear receptors increased ACSL3 levels in placental trophoblasts (which corresponded to fatty acid uptake [ 63] ), and PPAR ␦ regulated the expression of ACSL3 in hepatoma HepG2 cells ( 64 ). RNAi of ACSL3 in primary hepatocytes decreased the activity of PPAR ␥ and other lipogenic transcription factors ( 65 ).…”
Section: Lipid Droplet Biogenesismentioning
confidence: 99%
“…A positive correlation between placental LXR mRNA expression and placental free fatty acids was found in preeclampsia (Weedon-Fekjaer et al, 2010b).…”
Section: Lxrs In Placental Pathologiesmentioning
confidence: 88%